(untitled) (Englewood Cliffs, N.J., 1971)
Getting from here to there in the United States today can feel a lot closer to an episode of The Flintstones than The Jetsons. Every day we deal with problems that should be relics of the past: congested highways full of single-occupancy cars, mass transit systems continually under threat of service cuts, and aging infrastructure on the verge of obsolescence if not total collapse. For all humanity’s advances, our daily haul can still be a nightmarish experience that reduces productivity, increases stress, endangers public safety, and hastens global climate change.
Keywords: American transportation,Giao thông Hoa Kỳ